Regulation of the Coxsackie and adenovirus receptor expression is dependent on cystic fibrosis transmembrane regulator in airway epithelial cells. (16th September 2016) - Sharma, Anurag; Xu, Yaqin; Sung, Biin; Vincent, C. Theresa; Worgall, Tilla; Worgall, Stefan
Abstract: The coxsackievirus and adenovirus receptor (CAR), in addition to serving as viral receptor, is a component of tight junctions and plays an important role in tissue homeostasis. Defects in the cystic fibrosis transmembrane regulator (CFTR) in lung epithelial cells are linked to inflammation and susceptibility for respiratory tract infections. Here, we demonstrate that CAR expression and infectivity with adenovirus (Ad) are increased in cystic fibrosis airway epithelial cells. Inhibition of CFTR or histone deacetylase (HDAC) enhanced CAR expression while CFTR overexpression or restoration of the diminished HDAC activity in cystic fibrosis cells reduced CAR expression. This connects the CFTR to CAR expression and infectivity with adenovirus through HDAC.